Mutation-specific IDH1 antibody differentiates oligodendrogliomas and oligoastrocytomas from other brain tumors with oligodendroglioma-like morphology - Capper, David; Reuss, David; Schittenhelm, Jens; Hartmann, Christian; Bremer, Juliane; Sahm, Felix; Harter, Patrick N.; Jeibmann, Astrid; Deimling, Andreas von (Acta neuropathologica, 2011)
Isocitrate dehydrogenase 1 (IDH1) mutations are frequent in astrocytomas, oligoastrocytomas and oligodendrogliomas. We previously reported the generation of a mutation-specific antibody that specifically detects R132H mutated IDH1 protein (clone H09). Here, we investigate the feasibility of H09 immunohistochemistry to differentiate between oligodendrogliomas/oligoastrocytomas and other tumors with similar morphology. A total of 274 brain tumors presenting with focal or extensive clear cell morphology were investigated. High numbers of H09-positive cases were observed in adult grade II oligodendrogliomas (67 of 74, 91%), grade III oligodendrogliomas (65 of 69, 94%), grade II oligoastrocytomas (11 of 14, 79%) and grade III oligoastrocytomas (10 of 11, 91%). All cases of pediatric oligodendrogliomas (n = 7), neurocytomas (n = 41, 35 central, 4 extraventricular, 2 cerebellar liponeurocytomas), dysembryoplastic neuroepithelial tumors (n = 21), clear cell ependymomas (n = 8), clear cell meningiomas (n = 9) as well as 12 primary glioblastomas with oligodendroglial differentiation and 5 pilocytic astrocytomas with oligodendroglial-like differentiation were negative for H09 immunohistochemistry. Three oligodendrogliomas with neurocytic differentiation had evidence of IDH1/IDH2 mutations either by H09 immunohistochemistry or direct sequencing. We conclude that in tumors with an oligodendroglioma-like morphology, binding of H09 is highly specific for oligodendrogliomas or oligoastrocytomas and substantially helps in the discrimination from other clear cell tumors. Negative H09 immunohistochemistry of an adult oligodendroglioma or oligoastrocytoma should prompt the consideration of other clear cell neoplasms. Further, our observations firmly assign oligodendrogliomas with neurocytic differentiation to the group of oligodendrogliomas and demonstrate that H09 is especially helpful for the difficult discrimination of such lesions from extraventricular neurocytomas.